Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1074/jbc.m001452200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 30-Base Pair Regulatory Element and Novel DNA Binding Protein That Regulates the Human GLUT4 Promoter in Transgenic Mice

Abstract: We have previously demonstrated that the important cis-acting elements regulating transcription of the human GLUT4 gene reside within 895 base pairs (bp) upstream of the transcription initiation site (Thai, M. V., Guruswamy, S., Cao, K. T., Pessin, J. E., and Olson, A. L. (1998) J. Biol. Chem. 273, 14285-14292). Our studies demonstrated that an MEF2 binding site within this region was necessary, but not sufficient, for GLUT4 promoter function in transgenic mice. We have identified a second regulatory element (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 38 publications
4
105
1
Order By: Relevance
“…The GLUT4 gene is subjected to a complex system of tissuespecific and metabolic regulation. Two regulatory domains of the 5′-flanking DNA region are required to direct a complete programme of GLUT4 gene regulation [7][8][9][10]. The region referred to as domain II or myocyte enhancer factor 2 (MEF2) domain binds the isoforms of the MEF2 family of transcription factors (MEF2A, MEF2B, MEF2C and MEF2D) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The GLUT4 gene is subjected to a complex system of tissuespecific and metabolic regulation. Two regulatory domains of the 5′-flanking DNA region are required to direct a complete programme of GLUT4 gene regulation [7][8][9][10]. The region referred to as domain II or myocyte enhancer factor 2 (MEF2) domain binds the isoforms of the MEF2 family of transcription factors (MEF2A, MEF2B, MEF2C and MEF2D) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The first, a 513-amino acid protein called papillomavirus regulatory factor (Prf-1) and papillomavirus binding factor (PBF) was identified in a yeast one-hybrid assay for cellular proteins binding to the E2 binding site, P2, of human papillomavirus type 8 (29). The second factor, GLUT4-enhancer factor (G4EF), is highly similar to Prf-1/PBF and was identified as a 387-amino acid DNA-binding protein that recognizes the enhancer for the human GLUT4 transporter gene (30). On the basis of a CX 4 C-X 12 H-X 4 H sequence in the middle portion of each protein, both Prf-1/PBF and G4EF are proposed to contain a TFIIIA-like zinc finger DNA-binding domain.…”
Section: Figmentioning
confidence: 99%
“…GEF is a transcriptional activator that binds to domain I of the GLUT4 gene promoter (41,55). Coimmunoprecipitation and transient transfection assays demonstrated that GEF and MEF2A exert synergistic activation of the GLUT4 gene promoter by interacting with each other.…”
Section: Muscle-specific Glut4 Enhancer Factor (Gef)mentioning
confidence: 99%